PERAN PEMERINTAH KABUPATEN PEMALANG DALAM PELAKSANAAN PERATURAN DAERAH NO. 3 TAHUN 2011 (Konversi Lahan Pertanian Menjadi Non Pertanian di Kelurahan Wanarejan Selatan, Kecamatan Taman, Kabupaten Pemalang) - Rendi Kustriawan; Fitriyah .; Puji Astuti (Journal of Politic and Government Studies, 2016)
This research’s background is widespread use of agricultural land for non-agricultural building activities in Pemalang Regency, especially in South Wanarejan Village, Taman District, Pemalang Regency. It could have an impact on the lack of agricultural land, especially paddy fields is one issue that is closely related to production quantities of rice as the main staple food. This causes a lack of production, which in turn Indonesia to import rice. In this research will describe the amount of paddy fields that has been converted and the role of the Pemalang Regency Government in an effort to control the rate of conversion of existing paddy fields. According to the existing policy, Pemalang Regency Government has issued Regional Regulation No. 3 of 2011 on Spatial Planning, which also related to the control of agricultural land conversion.The research shows low commitment of Pemalang Regency Government enforcement to Regional Regulation No. 3 of 2011 on Pemalang Regency Spatial Planning in 2011 - 2031. This is caused by many obstacle factors such as no operation BKPRD in coordination functions, the lack of public knowledge about the Regional Regulation No. 3 of 2011, weak economic conditions of the Pemalang Regency Government for redressing existing illegal building, and no replacement land for building on inappropriate land according to regional regulations. In this research also shows Pemalang Regency community low involvement in efforts to control the rate of land conversion, even nothing either of the planning, formulation, implementation, as well as to the level of policy evaluation.Keywords: Control, Land Conversion, Role of Government, Community Role